CULTIVATION OF KISHMISH VARIETIES OF GRAPES FROM CUTTINGS IN CONDITIONS OF TASHKENT REGION (American Journal of Interdisciplinary Research and Development, 2022)
This article presents scientific-analytical data based on the results of the research carried out within the framework of the propagation of kishmish varieties of grapes from cuttings in the conditions of the Tashkent region. Also, the article provides information on the rootability and root system development of cuttings of kishmish varieties, growth parameters of seedlings of kishmish varieties grown from cuttings.